Brassinosteroid-BODIPY conjugates: Design, synthesis, and properties - Malachowska-Ugarte, Magdalena; Sperduto, Claudio; Ermolovich, Yuri V; Sauchuk, Alina L; Jurášek, Michal; Litvinovskaya, Raisa P; Straltsova, Darya; Smolich, Igor; Zhabinskii, Vladimir N; Drašar, Pavel; Demidchik, Vadim; Khripach, Vladimir A (Steroids, 2015)
Three BS-BODIPY (brassinosteroids-4,4-difluoro-4-bora-3a,4a-diaza-s-indacene) conjugates were synthesized and their fluorescent and immunological properties were investigated. Two of the conjugates, having present all the functional groups characteristic of BS, were shown to be potentially useful as biological probes to study involvement of BS into physiological processes in living cells.
Keywords: Boron Compounds; Brassinosteroids; sloučeniny boru; Epibrassinolide; BODIPY; Castasterone; brassinosteroidy; Conjugates; Epicastasterone